Variabel-Variabel yang Memengaruhi Lansia Bekerja Penuh Waktu di Indonesia Tahun 2020 - Kezia Sibuea; Suryanto Aloysius (Seminar Nasional Official Statistics, 2022)
Almost all countries in the world are experiencing population aging which is marked by an increasing number of elderly people, including Indonesia. However, the growth of the elderly population actually faces various challenges, especially from an economic perspective. This encourages the elderly to continue working in old age even with full working hours, even though the elderly should have enjoyed their old age. Therefore, this study aims to find out the overview of the elderly who work full time and find out the independent variables that significantly affect the elderly working full time in Indonesia in 2020 using binary logistic regression. The data used is the raw data of Sakernas (National Labor Force Survey) August 2020. The results showed that there were 47.6 percent of the elderly working full time in Indonesia in 2020. The variables that significantly influenced the elderly to work full time were gender, age, marital status, education level, status of head of household, area of residence and disability status.